Atypical Rapid Onset of Olmesartan-Induced Enteropathy with Recurrence After Rechallenging - Lila Bekkai; Aymen Ibn Majah; Laurine Verset; Lucas Jacobs; Charline Danneel; Okyay Elkilic; Frédéric Collart; Joëlle Nortier; Maxime Taghavi (Diseases)
Background: Olmesartan-induced enteropathy is a rare complication of a widely used angiotensin II receptor blocker. Patients usually present with chronic diarrhea and weight loss. Histologically, villous atrophy and intraepithelial lymphocyte infiltrates within the duodenum confirm the diagnosis. The prognosis is usually good after withdrawal of the offending drug. Case presentation: Here, we report the case of a 76-year-old woman who developed a severe form of Olmesartan-induced enteropathy complicated by acute kidney injury and acute recurrence after drug rechallenge. After definite cessation of the drug, the patient did not experience any gastrointestinal (GI) symptom recurrence after 6 months of follow-up. However, she experienced chronic kidney disease stage G3b. Histological analysis did not show any villous atrophy or intraepithelial lymphocyte infiltrates within the duodenum or the colon biopsy. Discussion and conclusion: This case highlights the broad spectrum of clinical manifestations and histological findings in Olmesartan-induced enteropathy. It also highlights the importance of rapid diagnosis in order to limit organ damage such as chronic kidney disease.